Search for resonance-enhanced 𝐶⁢𝑃 and angular asymmetries in the [Lambda]+ 𝑐 →𝑝⁢[mu]+[mu]- decay at LHCb - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review, 2025)
The first measurement of the 𝐶⁢𝑃 asymmetry of the decay rate (𝐴𝐶⁢𝑃) and the 𝐶⁢𝑃 average (Σ⁢𝐴FB) and 𝐶⁢𝑃 asymmetry (Δ⁢𝐴FB) of the forward-backward asymmetry in the muon system of Λ+𝑐 →𝑝⁢𝜇+⁢𝜇− decays is reported. The measurement is performed using a data sample of proton-proton collisions, recorded by the LHCb experiment from 2016 to 2018 at a center-of-mass energy of 13 TeV, which corresponds to an integrated luminosity of 5.4 fb−1. The asymmetries are measured in two regions of dimuon mass near the 𝜙-meson mass peak. The dimuon-mass integrated results are 𝐴𝐶⁢𝑃 =(−1.1 ±4.0 ±0.5)%, Σ⁢𝐴FB =(3.9 ±4.0 ±0.6)%, Δ⁢𝐴FB =(3.1 ±4.0 ±0.4)%, where the first uncertainty is statistical and the second systematic. The results are consistent with the conservation of 𝐶⁢𝑃 symmetry and the Standard Model expectations.
Veröffentlicht: 12. Mai 2025
Im Titel sind die Plus- und Minuszeichen hochgestellt sowie der Buchstabe "c" tiefgestellt
*LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, C. Langenbruch, B. Leverington, J. Marks, S.R. Roy, M. Ruiz Diaz, M.D. Tat, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1123 weitere Personen]
Gesehen am 13.11.2025